Potential of Volatile Organic Compound (VOC) and Serum Interleukin-17 for Evaluation of Lung Cancer Therapy Based on Response Evaluation Criteria in Solid Tumors (RECIST) - Permatasari, Adinda Pramitra; Setyawan, Ungky Agus; Rakhma, Sastia; Djajalaksana, Susanthy; Wardoyo, Arinto Yudi Ponco (Indonesian Journal of Cancer, 2024)
Background: Lung cancer is the second leading cause of death in the world due to delays in diagnosis. Non-invasive Volatile Organic Compound (VOC) method to diagnose and monitor the progressivity of lung cancer. Interleukin-17 (IL-17) has an important role in the progression and treatment of lung cancer. Objective evaluation of chemotherapy using Response Evaluation Criteria in Solid Tumors (RECIST 1.1). This study aims to determine the relationship between VOC, IL-17, and lung cancer chemotherapy response based on RECIST at Saiful Anwar General Hospital, East Java.Methods: In a prospective cohort study, 47 lung cancer patients received first-line chemotherapy pre and post-three series of chemotherapy. Exhaled breath was collected with Tedlar Bags and then analyzed with µβreath for VOC. IL-17 in blood serum is determined by an enzyme-linked immunosorbent assay (ELISA). The data were analyzed using the Wilcoxon, Mann-Whitney, and Spearman tests.Results: There were significant in VOC Components (p 0.05) Formaldehyde (CH2O), Toluene (C7H8), Acetone (C3H6O), Hexane (C6H14), Methane (CH4), RECIST non-target lesions, and new lesions pre and post-three series of chemotherapy but not found in IL-17. Acetone (C3H6O) pre and Methane (CH4), IL-17 post-three series of chemotherapy based on RECIST Overall Response (OR) found significant. The analysis showed a positive correlation between Formaldehyde (CH2O) pre and Methane (CH4), IL-17 post-three series of chemotherapy based on RECIST OR, but a negative correlation between Acetone (C3H6O) pre-chemotherapy. Conclusions: There was a significant decrease in formaldehyde, toluene, hexane, methane and an increase in acetone in lung cancer patients pre and post-three series of chemotherapy. There was a significant relationship between formaldehyde, acetone pre-chemotherapy, and methane, IL-17 post-three series of chemotherapy based on the RECIST overall response